2015
DOI: 10.1007/s10533-014-0064-1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in soil organic matter after a decade of nutrient addition in a lowland tropical forest

Abstract: Soil organic matter is an important pool of carbon and nutrients in tropical forests. The majority of this pool is assumed to be relatively stable and to turn over slowly over decades to centuries, although changes in nutrient status can influence soil organic matter on shorter timescales. We measured carbon, nitrogen, and phosphorus concentrations in soil organic matter and leaf litter over an annual cycle in a long-term nutrient addition experiment in lowland tropical rain forest in the Republic of Panama. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 66 publications
5
53
2
Order By: Relevance
“…Turner et al [50] found a similar increase in soil C during the dry season in a more strongly seasonal forest on Barro Colorado Island in Panama. However, we did not observe a significant increase in soil N whereas the study in Panama did [50].…”
Section: Effects On Soil Nitrogen and Carbonmentioning
confidence: 75%
“…Turner et al [50] found a similar increase in soil C during the dry season in a more strongly seasonal forest on Barro Colorado Island in Panama. However, we did not observe a significant increase in soil N whereas the study in Panama did [50].…”
Section: Effects On Soil Nitrogen and Carbonmentioning
confidence: 75%
“…Soil C might on average originate predominantly from roots rather than shoots (Rasse et al, 2005), and that may be the case in our soils in Panama because although changes in litter inputs have caused changes in soil C, they are small -approximately 1 % of total soil C per year -compared to the "normal" turnover of C of 25 % (0-10 cm soil) within 6 months (as calculated from changes in C concentration from wet season to dry season; Turner et al, 2015) and an annual turnover of about 7 % based on incorporation of 13 C into soils over decades (Schwendenmann and Pendall, 2008). Turnover rates of soil C are also high in other tropical forests; for example, in eastern Brazil 40-50 % of the C in the top 40 cm of soil had been fixed in about 32 years (Trumbore, 2000).…”
Section: Soil Carbon Dynamicsmentioning
confidence: 95%
“…Carbon in tropical forest soils is dynamic: Schwendenmann and Pendall (2008) reported a turnover time of 15 years for the "slow" pool of soil C, comprising 38 % of the total soil C, in the top 10 cm of soil in semi-evergreen rain forest on Barro Colorado Island, Panama (61 % of total soil C was "passive" with a turnover time of the order of a 1000 years). Turner et al (2015) reported an approximate 25 % increase in soil C from one dry season to the next wet season in the top 10 cm of soil on the Gigante Peninsula in Barro Colorado Nature Monument, Panama, at a site close to the current litter manipulation experiment. Thus, there is the potential for the amount of C in tropical soils to change over only a few years, with potentially important consequences for atmospheric CO 2 concentrations.…”
Section: Introductionmentioning
confidence: 92%
“…1100 g m −2 , with c . 60% falling as leaves (Wright et al ., ; Turner et al ., ). The B stock is calculated on the basis of two‐thirds of the total leaf litter falling in the dry season.…”
Section: Resultsmentioning
confidence: 97%
“…Boron is similar to P in terms of its distribution in the tropical forest soil studied here: soluble concentrations are < 1 mg kg −1 , while total concentrations are primarily contained in recalcitrant forms that are not directly available to plants (compare Table with values for total and soluble P on Gigante Peninsula) (Turner et al ., , ). However, comparison of B in rainfall and leaf litter fall provides support for our assertion that B is unlikely to be of importance in structuring the vegetation in lowland tropical forests.…”
Section: Discussionmentioning
confidence: 99%